Al-Quran-Based Indonesian Language Learning Model from a Communication Science Perspective to Improve Madrasah Student Literacy - Musafir, Ahmad; Sulkifli, Sulkifli; Akbar, Fadly (Journal of Indonesian Islamic Studies, 2025)
This study aims to develop and analyze an Indonesian language learning model based on Qur’anic values from the perspective of communication science to enhance literacy among Madrasah students. The research addresses the integration of Islamic principles into language education while emphasizing the role of communication processes in delivering effective learning. Using a Research and Development (R&D) approach, the study involves designing the model, implementing it in Madrasah classrooms, and evaluating its effectiveness in improving students’ literacy skills. Data were collected through classroom observations, student assessments, and teacher interviews, then analyzed using descriptive and inferential techniques. The findings indicate that the Qur’anic-based model, grounded in communication theory, significantly improves students’ reading, writing, and comprehension skills while fostering an understanding of Islamic values. The study provides evidence that integrating communication principles and Qur’anic values in Indonesian language learning can enhance literacy outcomes and contribute to a holistic educational framework in Islamic schools